CoREST: A functional corepressor required for regulation of neural-specific gene expression - Andrés, María E. (The National Academy of Sciences, 1999)
Several genes encoding proteins critical to the neuronal phenotype, such as the brain type II sodium channel gene, are expressed to high levels only in neurons. This cell specificity is due, in part, to long-term repression in nonneural cells mediated by the repressor protein REST/NRSF (RE1 silencing transcription factor/neural-restrictive silencing factor). We show here that CoREST, a newly identified human protein, functions as a corepressor for REST. A single zinc finger motif in REST is required for CoREST interaction. Mutations of the motif that disrupt binding also abrogate repression. When fused to a Gal4 DNA-binding domain, CoREST functions as a repressor. CoREST is present in cell lines that express REST, and the proteins are found in the same immunocomplex. CoREST contains two SANT (SW13/ADA2/NCoR/TFIIIB B) domains, a structural feature of the nuclear receptor and silencing mediator for retinoid and thyroid human receptors (SMRT)-extended corepressors that mediate inducible repression by steroid hormone receptors. Together, REST and CoREST mediate repression of the type II sodium channel promoter in nonneural cells, and the REST/CoREST complex may mediate long-term repression essential to maintenance of cell identity.